AFRICAN-AMERICAN WOMEN’S POWER IN MARGOT LEE SHETTERLY HIDDEN FIGURES - Scarlet Rumbayan; Tini Mogea; Imelda Lolowang (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this research is to reveal about African-American Women's Power in Margot Lee Shetterly Hidden Figures.  In this study the author will use qualitative research because the data to be collected is in the form of words.  In analyzing the novel, the author uses a sociological approach and the theory of sociology of literature proposed by Alan Swingwood.  Therefore, based on the findings found in this novel, there are several things that represent the strength of African-American women in facing all acts of discrimination that they experience in the work environment at NASA and in their social lives.  There is strength as a woman who is brave, persistent and has good self-defense.  Based on the research that has been done, this can provide many lessons for everyone, especially women to be able to further improve their own abilities, there are also suggestions and input for every reader who reads this research, namely: 1) It is highly recommended for students of the Department of English Education to  may use this as an appropriate reference for other relevant research studies.  2) For women, this research further raises the power of women not only as a mother but also being able to do anything according to their respective abilities and preferences.  3) For the Department of English Education, this research is proof that we can learn character learning through literary works, for example the novel Hidden Figures which raises many important issues that are closely related to today's life.